2004
DOI: 10.1093/humrep/deh321
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion-related readmissions following gynaecological laparoscopy or laparotomy in Scotland: an epidemiological study of 24 046 patients

Abstract: With the exception of laparoscopic sterilizations, open and laparoscopic gynaecological surgery are associated with comparable risks of adhesion-related readmissions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
124
0
8

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(138 citation statements)
references
References 17 publications
4
124
0
8
Order By: Relevance
“…Surgeons participating in the inclusion of patients in the COLOR trial had all performed 20 laparoscopic colonic resections before entering the trial. The protocol for the COLOR trial was approved by the appropriate ethics committee of each participating institution before its entry into the trial, and the details of inclusion, exclusion, and consent have been described [12]. Patients were included in the trial according to the inclusion and the exclusion criteria, and of the initially 1,248 included patients 1,083 patients were left for follow-up, as described [19].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Surgeons participating in the inclusion of patients in the COLOR trial had all performed 20 laparoscopic colonic resections before entering the trial. The protocol for the COLOR trial was approved by the appropriate ethics committee of each participating institution before its entry into the trial, and the details of inclusion, exclusion, and consent have been described [12]. Patients were included in the trial according to the inclusion and the exclusion criteria, and of the initially 1,248 included patients 1,083 patients were left for follow-up, as described [19].…”
Section: Methodsmentioning
confidence: 99%
“…In an experimental model in pigs, it was reported recently that the incidence of intra-abdominal adhesions was lower after laparoscopic compared with open cholecystectomy [11]. It has been reported that open and laparoscopic surgery are associated with comparable risks of adhesion-related readmissions after gynecological surgery [12]. Hypothetically the minimally invasive techniques may result in less adhesion formation compared with open techniques.…”
mentioning
confidence: 99%
“…The SCAR group subsequently reported that for therapeutic and diagnostic laparoscopic procedures (i.e. all laparoscopic procedures undertaken with the exception of low-risk tubal sterilisations), the risk of adhesion-related readmission was comparable to that of gynaecological laparotomy [5]. The group concluded that despite advances in surgical technique, the burden of adhesion-related readmissions continues.…”
Section: The Epidemiology and Clinical Importance Of Adhesionsmentioning
confidence: 99%
“…Despite advances in surgical techniques in recent years, the burden of adhesion-related complications has not changed [4,5]. While laparoscopic procedures are commonly believed to be less adhesiogenic and cause fewer de novo adhesions to form compared to open surgery [6,7], for many procedures, the comparative risk of adhesion-related complications following open and laparoscopic gynaecological surgery is similar [5].…”
Section: Introductionmentioning
confidence: 99%
“…The most common site of postoperative adhesions formation is between the ovary and the pelvic wall [12]. Notwithstanding the advances in surgical techniques [13] and the use of surgical anti-adhesive agents, the incidence of adhesion-related complications do not seem to have significantly declined [14].…”
Section: Introductionmentioning
confidence: 99%